A new genus of anthophilous drosophilids, Impatiophila (Diptera, Drosophilidae): morphology, DNA barcoding and molecular phylogeny, with descriptions of thirty-nine new species - Fu, Zhao; Toda, Masanori J.; Li, Nan-Nan; Zhang, Ya-Ping; Gao, Jian-Jun (Zootaxa, 2016)
Breeding habits of essential dependence on flowers for larval food resources have evolved repeatedly in separate lineages of the Drosophilidae. However, flowers of Impatiens L. have never been recognized as hosts for drosophilid flies until recently: two Hirtodrosophila species, H. actinia (Okada) and H. yapingi Gao, were found feeding and breeding on Impatiens flowers. During our recent field surveys in central and southern China, a great number of drosophilid flies morphologically resembling the two species were collected, almost exclusively from flowers of Impatiens (family Balsaminaceae) and the family Gesneriaceae. In the present study, these specimens were identified on the basis of morphological characters and/or partial DNA sequences of the mitochondrial COI (cytochrome c oxidase subunit I gene, used as a barcoding marker). As a result, 39 new species were recognized. We then reconstructed the phylogenetic relationships among most of them, based on concatenated DNA sequences (3047 nucleotide sites) of two mitochondrial (COI and COII, i.e., cytochrome c oxidase subunits I and II, respectively) and three nuclear genes (ATPsyn-alpha, alphaTub84B and Hsc70cb, i.e., ATP synthase alpha, alpha-Tubulin at 84B and Hsc70Cb isoform H, respectively). In the resulting Bayesian and ML (maximum likelihood) trees, three well-supported clades were recognized, with a few species having remained uncertain for their phylogenetic positions. We also conducted a cladistic analysis with data of adult morphological characters to investigate the phylogenetic positions of a few species of which DNA sequence data were not available, and to investigate the classification of species groups with definition of their diagnoses. In consequence, we established a new genus, Impatiophila, for the species visiting flowers of Impatiens and Gesneriaceae, described all the new species, and revised the taxonomy of some known species.